Tracing Cultural Acculturation in the Shophouse Architecture of Tuban's Arab Neighborhood - Cynthia Puspitasari; Anedya Wardhani (Architectural Research Journal, 2025)
This research examines the cultural acculturation reflected through the architecture of shophouse buildings in Arab Village, Tuban, East Java. This study explores how Javanese, Arab (Yemeni), Chinese, and Dutch Colonial architectural elements blend over time in the spatial and visual form of shophouse buildings that double as residential and business premises. Using a descriptive qualitative approach, data was collected through visual observation, architectural sketches, interviews with long-time residents, and analysis of archives and historical documents. The results showed that the acculturation process occurred both in physical elements-such as building typology, spatial layout, facade composition, roof shapes, and ornaments-and non-physical aspects, such as trade practices, gender roles, and cultural values in daily life. Acculturation in physical forms is more easily accepted, while non-physical aspects such as lifestyle and social behavior tend to maintain stronger cultural boundaries. The area's architectural identity reflects a gradual hybridization process driven by functional needs, cultural interaction and urban transformation, making the built heritage a meaningful medium for cultural dialogue and identity preservation.